Effect of Terroir on Phenolic Content and Aroma Properties of Grapes and Wines - Yuyuen Phajon; Hongbing Tan; Bochen Liu; Yang Zhang; Yanlun Ju; Tian Shen; Meilong Xu; Yulin Fang (Foods, 2025)
Ten vineyards, belonging to five wine regions, were selected in this study. Maturity indicators and phenolic and aromatic compounds were measured to investigate relationships with factors related to the terroir, including climate conditions and soil nutrients. Multiple factor analysis of all compositions showed that different wine regions or vineyards had different characteristics, which were partly associated with the terroir. The results showed that Shizuishan had high sugar content. A high level of anthocyanins could be found in Qingtongxia and Yongning, respectively. Moreover, Qingtongxia had higher concentrations of monomeric phenols in grapes than the others. LSYH (Lanshanyunhao) and LL (Lilan) had higher YAN (yeast assimilable nitrogen) content and pH in grapes, but their wine had a green flavor (high concentration of alcoholic volatile compounds). The Shizuishan and Hongsipu wine regions had fruitier flavors (high concentration of ester volatile compounds). This study demonstrated the characteristics of different vineyards and wine regions, providing a direction for the future development of region-specific grapes and wines.